Institutions and economic performance in Africa: A comparative analysis of Mauritius, Botswana and Uganda - Kiiza, Julius (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper examines the relationship between institution building and economic performance in Mauritius, Botswana and Uganda. The rationale for comparing these cases is simple. While the three have been super-economic stars in their own right, they have achieved substantially different outcomes. Mauritius has achieved Asia-type rapid growth, backed by the structural transformation of the economy from colonial commodity production (sugar) to postcolonial higher value-added industrial and information outcomes. Botswana has delivered rapid and sustained growth with no structural economic transformation. Uganda has attained rapid growth for a shorter postcolonial period (since 1992) and with no structural transformation. This paper contends that these cross-national differences largely arise from the presence of developmental nationalism plus Weberian bureaucracies in Mauritius and Botswana, and their absence in Uganda.
Keywords: Developmental nationalism; Economic performance; Africa